Surgical oncology of the head and neck district during COVID-19 pandemic - Salzano, Giovanni (Eur Arch Otorhinolaryngol, 2021)
PURPOSE: A new member of the Coronaviridae family caused a worldwide pandemic emergency called Coronavirus disease 2019 (COVID-19). Health care workers who come into contact with the upper aero-digestive tract during diagnostic and therapeutic procedures, such as otolaryngologists, oral and maxillofacial surgeons, and head and neck surgeons, may undergo profound changes in their activities and are particularly at risk. We analysed the impact of COVID-19 on our oncological surgical activity. METHODS: To address the emergency and guarantee safety of patients referred to our Unit, reproducible guidelines were followed. Surgical activity data during COVID-19 were compared to previous years (2018 and 2019). RESULTS: From 21st February to 25th of May 113 surgical procedures were performed. The average of the two selected years (2018–2019) is 84.5, showing an increase of 34.5% of our activities (statistically significant, p = 0.0011). No patient showed perioperative or postoperative contagion. CONCLUSION: Due to the conversion of regular Hospitals into COVID Centers, Cancer Centers may encounter an increased demand for procedures. Following strict guidelines, it seems possible to face surgical activity on cancer patients and respect standard procedures aimed at containing the spread of COVID-19 infection.